PENGARUH KAPABILITAS USAHA DAN KEUNGGULAN BERSAING TERHADAP ORIENTASI EKSPOR BATIK JAMBI - Ade Octavia (DIGEST MARKETING, 2012)
Business capability and competitive advantages is important to be developed mainly to in oreder to enter export market. The purpose of this study is examined and analyzes the effect of the two variabel. Survey is used to conduct research, and the respondents are batiks firms’ manager. The result shows that there is no relationship of business capability on export orientation instead of competitive advantage.